Two new species of eriophyoid mites (Acari: Eriophyoidea) associated with Elaeagnaceae in Turkey - Deni̇zhan, Evsel; Monfreda, Rosi̇ta; de Li̇llo, Enri̇co; Çobanoglu, Sultan (Zootaxa, 2008)
Turkish populations of eriophyid mites infesting Elaeagnaceae were examined. Two new species are described and illustrated: Anthocoptes cellatus n. sp. was collected on Hippophae rhamnoides L. (seaberry), and Aceria angustifoliae n. sp. was found on Elaeagnus angustifolia L. (Russian olive). A remark on mite mounting was made.